Immunological Tolerance and Function: Associations Between Intestinal Bacteria, Probiotics, Prebiotics, and Phages - Vitetta, Luis; Vitetta, Gemma; Hall, Sean (Frontiers in Immunology, 2018)
Post birth there is an assault on all mucosal surfaces including the skin. The intestinal microbiome is an important participant in health and disease. The pattern of composition and concentration varies greatly. Therefore achieving immunological tolerance in the first three-four years of life is critical for maintaining health throughout a lifetime. Probiotic bacteria are organisms that afford beneficial health effects to the host and in certain instances may protect against the development of disease. The potential benefits of modifying the composition of the intestinal microbial cohort for therapeutic benefit is evident in the use in high risks groups such as premature infants, traveller’s diarrhoea, children receiving antibiotics and in rotavirus infections. Probiotics and prebiotics are postulated to have immunomodulating capabilities by influencing the intestinal microbial cohort and dampening the activity of pathobiont intestinal microbes, such as Escherichia coli and Clostridia perfringens. Lactobacilli and Bifidobacteria are examples of probiotics found in the large intestine and so far, the benefits afforded to probiotics have varied in efficacy. Most likely the efficacy of probiotic bacteria has a multifactorial dependency, namely on a number of factors that include agents used, the dose, the pattern of dosing, and the characteristics of the host and the underlying luminal microbial environment and the activity of bacteriophages. Bacteriophages display an effective local protective control mechanism for the intestinal barrier against commensal pathobionts by establishing a symbiotic relationship with the host. This co-operation is an immunological defence mechanism that exploits bacteriophage–mucin glycoprotein interactions that controls bacterial diversity and abundance as for example in the mucin layers of the gut. Moreover, and importantly the efficacy of probiotics may be dependent on the symbiotic incorporation of prebiotics, and just how abundant and diverse the intestinal virome (e.g., temperate phages) and the predilection for specific bacterial species.